Gallstone Ileus: A Rare Surgical Emergency - Ullah, AZM Forman; Nasim, Md Muzharul Hoq; Salam, Abdus; Tayeb, Md (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2022)
Background : Gallstone ileus is a rare complication of cholelithiasis and is an uncommon cause of intestinal obstruction accounting for 1%–4% of mechanical bowel obstructions. This usually results from luminal impaction of one or more gallstone. Case Presentation : A 86-year-old male presented with the history of bilious vomiting for 15 days and abdominal distension for 8 days and diagnosed as a case of intestinal obstruction due to gall stone ileus. He was treated surgically by laparotomy followed by enterotomy and removal of gall stone were performed from the proximal ileum. Conclusion : Early diagnosis and treatment are important otherwise adverse effect of mechanical bowel obstruction leads to bad prognosis. Chatt Maa Shi Hosp Med Coll J; Vol.21 (2); July 2022; Page 57-59